Fulfilling the promise of Palermo? A political history of the un convention against transnational organized crime - Ian Tennant (Journal of Illicit Economies and Development (JIED), 2020)
UNTOC created a legally binding instrument governing international cooperation between law enforcement and judicial authorities to share evidence and pursue international criminal actors, and a framework for countries to update their legislation to be better able to investigate and prosecute such criminals. Its impact as a step-change in the legal framework against transnational organized crime is widely acknowledged. The paper highlights that the UNTOC did in fact bring those anti-drug and anti-crime efforts at the UN closer together, in spite of their different histories and personnel. However, the disparity between the political momentum and achievements of the late 1990s, compared to the Convention's journey since its entry into force in 2003 is stark. Further, the level of coordination amongst all UN processes on drugs and crime issues still leave significant room for improvement. This paper analyses the political history of UNTOC, using an array of newly conducted in-depth interviews with key protagonists to understand their views on its development, subsequent implementation and potential future promise. The paper offers some suggestions on how the international community can move forward its collective efforts on achieving the Convention's aims and thereby fulfilling the promises made in Palermo.
Keywords: 330; civil society; multilateral; organized crime; politics; UN